Characterization of Schiff base self-healing hydrogels by dynamic speckle pattern analysis - Madeh Sajjadi; Ramin Jamali; Tahereh Kiyani; Zahra Mohamadnia; Ali-Reza Moradi (Scientific Reports, 2024)
Abstract Self-healing hydrogels are emerging materials capable of restoring functionality after damage, making them highly suitable for biomedical applications, such as tissue engineering, wound healing, and drug delivery. In this study, we synthesize and characterize a novel biodegradable, conductive, and self-healing hydrogel. The synthesis is based on a Schiff base formed between gelatin and hyaluronic acid, and the dynamic reversible Schiff base bond provides the self-healing property. To characterize and assess the self-healing behavior of the hydrogel, dynamic speckle pattern (DSP) analysis is introduced as a non-destructive, non-contact, and easy-to-implement method. Speckle patterns are formed upon scattering of laser light from a diffusive matter and includes a huge overall information about the sample, to be extracted by statistical processing. DSP analysis is employed to monitor the self-healing process of the hydrogel at both macroscopic and microscopic scales. Experimental procedure involve in situ acquisition of speckle patterns over time under controlled environmental conditions, followed by statistical analysis to evaluate the internal dynamics of the healing process. Several statistical parameters are computed for real-time monitoring of the self-healing property of the hydrogel. The findings, on the one hand, underscore the potential of Schiff base hydrogels in advanced biomedical applications where self-healing properties are critical for sustained performance and longevity. On the other hand, the introduced analysis method shows its potential to serve as an effective approach for biomaterial characterization.